THE ROLE OF TWITTER IN DISCUSSING THE ISSUE OF DEPRESSION - Mohamad Shafiei Ayub; Muhammad Syafi Fauzan Saifuddin; Muhammad Naeem Mohd Razman; Muhammad Nur Iman Anuar; Darwisy Zakwan Khairudin; Muhammad Haziq Hamzah; Muhammad Syawal Sazali; Nurshaza Farah Md Sharif, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The prevalence of depression or mental health problems among Malaysians has been quite worrying since the occurrence of Covid-19 pandemic followed by the Movement Control Order (MCO) imposed by the government to curb the pandemic. Awareness about mental health problems has become more popular and news about it often spreads across newspapers and other mass media. Moreover, the emergence of various kinds of new media during this era of fourth industrial revolution plays a role in influencing the people’s perception. One of the most influential new media is Twitter which has the advantage of becoming one of the most popular and far-reaching social media platforms. It has indirectly provided space for them to use Twitter to exchange their opinions and views regarding mental health problems. Hence, the influence of Twitter on mental health issues has become very significant and needs to be investigated. Therefore, a preliminary study was conducted to identify the role of Twitter in influencing people as well as the function of Twitter in helping people dealing with the problem of depression. This study used a qualitative method where data collection methods such as library research methods, interview methods and text analysis methods were employed. In addition, this study also used a data analysis method. The results of the study found that Twitter as a very influential medium to spread information and programs related to mental health, share experiences or anything issues pertaining to depression. In addition, the function of threads in Twitter facilitates the search for information sources related to depression. In conclusion, new media such as Twitter is very impactful as a medium of spreading awareness and knowledge in dealing with the problem of depression in the community.